FAKTOR YANG MEMPENGARUHI LOYALITAS KARYAWAN DI HOTEL DYAN GRAHA PEKANBARU - Silvi Ika Rinanda; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aimed about employee’s loyality at Dyan Graha Hotel Pekanbaru. This research aims to: (1) to know about employee’s loyality. (2) to know the multi way to increase employee’s motivation at Dyan Graha Hotel Pekanbaru.This research was used descriptive quantitatif method to describe the issues. The sample used in this research was 56 people.The results of this research indicate that based on the research results obtained on the employee’s loyality at Dyan Graha Hotel Pekanbaru good. This is evidenced by the acquisition of the overall total score of all factors, which is 3.829points.Keywords: Loyality, employee, loyality factor.